2016
DOI: 10.1055/s-0042-107357
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Hydroxypropyl-β-Cyclodextrin-Based Extract of Medicago sativa in the Treatment of Mucopolysaccharidoses

Abstract: Mucopolysaccharidoses are inherited metabolic disorders resulting in the dysfunction of enzymes involved in the degradation of glycosaminoglycans, leading to severe clinical symptoms and a significantly shortened life span of patients. Flavonoids are recognized as glycosaminoglycan metabolism modulators, able to correct glycosaminoglycan cell storage. Therefore, the aim of this work was the development of an efficient and eco-friendly extraction process of phytochemicals from by simultaneous use of ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This is due partially to the effect of HPBCD acting synergistically with the complexed compound. In fact, it shows moderate GAGs restoration (198  μ g·mL −1 ) for its capability to form hydrogen bonds with polysaccharides, as GAGs [19]. From this result, the potential role of HP-betaCD as a therapeutic agent also emerges for the prevention and treatment of a group of metabolic disorders in which abnormal accumulations of GAGs occur.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due partially to the effect of HPBCD acting synergistically with the complexed compound. In fact, it shows moderate GAGs restoration (198  μ g·mL −1 ) for its capability to form hydrogen bonds with polysaccharides, as GAGs [19]. From this result, the potential role of HP-betaCD as a therapeutic agent also emerges for the prevention and treatment of a group of metabolic disorders in which abnormal accumulations of GAGs occur.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior can lead to increased in vivo ERT release and to the improvement of its bioavailability and activity. In addition, according to the literature [19, 20], an intrinsic activity of HP-betaCD on GAGs restoration also emerges, indicating its potential function in the treatment and prevention of many diseases associated with the imbalance of GAGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Fumić et al [ 70 ] proposed a novel MPS therapy using compounds of plant origin. They developed an efficient chemical process to obtain a Medicago sativa extract using ultrasound extraction and hydroxypropyl-β-cyclodextrin complexation.…”
Section: Compounds With Antioxidant Activities and Their Effects In Mpsmentioning
confidence: 99%
“…In a recent study performed by Fumić et al ( 2017 ), a highly active and purified extract of flavonoids from Medicago sativa has been obtained. These authors have confirmed that pure genistein is effective in reduction of GAG levels in MPS III cells (they did not specify what subtypes of Sanfilippo disease were studied), and demonstrated similar (but about 25% lower) activity of the flavonoids’ extract.…”
Section: Recent Studies On Cellular Models Of Mps IIImentioning
confidence: 99%